2020
DOI: 10.1590/2317-1545v42239839
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects during seed germination of Erythrina velutina Willd. under different temperatures (Part 1): reserve mobilization

Abstract: Erythrina velutina Willd. (Fabaceae) is a tree species that bears social, ecological, and economic importance for northeastern Brazil, a region with frequent temperature variations. The objective of this work was to evaluate the mobilization of reserves during seed germination and seedling establishment of E. velutina at different temperatures, and how these mechanisms are affected in a thermal-stress situation. The seeds germinated at 5, 15, 25, 35, and 45 °C, and the physiological and biochemical aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Regarding the temperatures within the storage times, it was observed that the temperature of 30 ºC provided an improvement in the percentage of germination, especially when the seeds were stored for 180 days. Higher temperatures increase the speed of chemical reactions accelerating the germination process (Felix et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the temperatures within the storage times, it was observed that the temperature of 30 ºC provided an improvement in the percentage of germination, especially when the seeds were stored for 180 days. Higher temperatures increase the speed of chemical reactions accelerating the germination process (Felix et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…An additional reason for the relatively higher abundance of glycosylated alkaloids in seeds of E. velutina is the fact that lipids represent the second most abundant reserve in this species. Lipid reserve mobilization may generate hydrogen peroxide during germination and early seedling establishment, particularly at higher temperatures [30] , [31] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Salienta-se que a germinação das sementes pode ser influenciada por uma série de fatores, tais como a umidade, temperatura, substrato, oxigênio e luz (Carvalho et al, 2020;Felix et al, 2020). Uso de quantidade excessiva de água, ou seja, de umidade no substrato durante a germinação pode influenciar negativamente, com diminuição significativa na germinação, segundo Piña-Rodriguez; Figliolia; , durante essa fase a umidade deve ser mantida constante para não influenciar no potencial germinativo da semente.…”
Section: Introductionunclassified